Specific antidotes against direct oral anticoagulants: A comprehensive review of clinical trials data. (1st July 2016) - Tummala, Ramyashree; Kavtaradze, Ana; Gupta, Anjan; Ghosh, Raktim Kumar
Abstract: The Vitamin K antagonist warfarin was the only oral anticoagulant available for decades for the treatment of thrombosis and prevention of thromboembolism until Direct Oral Anticoagulants (DOACs); a group of new oral anticoagulants got approved in the last few years. Direct thrombin inhibitor: dabigatran and factor Xa inhibitors: apixaban, rivaroxaban, and edoxaban directly inhibit the coagulation cascade. DOACs have many advantages over warfarin. However, the biggest drawback of DOACs has been the lack of specific antidotes to reverse the anticoagulant effect in emergency situations. Activated charcoal, hemodialysis, and activated Prothrombin Complex Concentrate (PCC) were amongst the nonspecific agents used in a DOAC associated bleeding but with limited success. Idarucizumab, the first novel antidote against direct thrombin inhibitor dabigatran was approved by US FDA in October 2015. It comprehensively reversed dabigatran-induced anticoagulation in a phase I study. A phase III trial on Idarucizumab also complete reversal of anticoagulant effect of dabigatran. Andexanet alfa (PRT064445), a specific reversal agent against factor Xa inhibitors, showed a complete reversal of anticoagulant activity of apixaban and rivaroxaban within minutes after administration without adverse effects in two recently completed parallel phase III trials ANNEXA-A and ANNEXA-R respectively. It is currently being studied in ANNEXA-4, a phase IV study. Aripazine (PER-977), the third reversal agent, has shown promising activity against dabigatran, apixaban, rivaroxaban, as well as subcutaneous fondaparinux and LMWH. This review article summarizes pharmacological characteristics of these novel antidotes, coagulation's tests affected, available clinical and preclinical data, and the need for phase III and IV studies. Highlights: Dabigatran, rivaroxaban, apixaban and edoxaban approved DOACs in USA Idarucizumab, antidote against dabigatran approved October 2015 Andexanet alfa, antidote against factor Xa inhibitors completed phase III trial Antidotes nonimmunogenic and do not cause reverse thrombosis